A review on presence, survival, disinfection/removal methods of coronavirus in wastewater and progress of wastewater-based epidemiology (2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused the global pandemic coronavirus 2019 disease (COVID-19). The outbreak of COVID-19 as Public Health Emergency of International Concern is declared by World Health Organization on January 30, 2020. The known route of transmission is due to direct contact or via respiratory droplets. Recently, several studies reported SARS-CoV-2 ribonucleic acid (RNA) in wastewater treatment plant samples. The presence of SARS-CoV-2 RNA in wastewater may predict COVID-19 occurrence qualitatively and quantitatively. The concept is known as wastewaterbased epidemiology (WBE) or sewage epidemiology. The present study reviewed the presence of coronavirus in wastewater and investigations relating to WBE development as a tool to detect COVID-19 community transmission. Few articles reported a correlation of SARS-CoV-2 RNA concentration in wastewater with the number of COVID-19 cases, whereas few reported higher prediction by wastewater surveillance than confirmed cases. The application of WBE is still in a preliminary stage but has the potential to indicate an early sign of transmission. The knowledge of persistence of coronavirus in municipal and hospital wastewater is needed for the application of WBE and to understand the chances of transmission. The studies reported more prolonged survival of coronavirus in lowtemperature wastewater. Studies relating to the inactivation of coronavirus by disinfectants and removal of coronavirus are also presented. Research on the performance of the commonly adopted disinfection technologies in inactivating SARS-CoV-2 in municipal and hospital wastewater is required to reduce the risk associated with municipal and hospital wastewater.